Cannabinoid Receptors in the Central Nervous System: Their Signaling and Roles in Disease - Kendall, Debra A.; Yudowski, Guillermo A. (Frontiers in Cellular Neuroscience, 2017)
The identification and cloning of the two major cannabinoid (CB¬1 and CB2) receptors together with the discovery of their endogenous ligands in the late 80s and early 90s, resulted in a major effort aimed at understanding the mechanisms and physiological roles of the endocannabinoid system (ECS). Due to its expression and localization in the central nervous system (CNS), the CB1 receptor together with its endogenous ligands (endocannabinoids) and the enzymes involved in their synthesis and degradation, has been implicated in multiple pathophysiological events ranging from memory deficits to neurodegenerative disorders among others. In this review, we will provide a general overview of the endocannabinoid system with emphasis on the CB1 receptor in health and disease. We will describe our current understanding of the complex aspects of receptor signaling and trafficking, including the non-canonical signaling pathways such as those mediated by β-arrestins within the context of functional selectivity and ligand bias. Finally, we will highlight some of the disorders in which CB1 receptors have been implicated. Significant knowledge has been achieved over the last 30 years. However, much more research is still needed to fully understand the complex roles of the endocannabinoid system, particularly in vivo, and to unlock its true potential as a source of therapeutic targets.